INVESTIGATION OF ADVANCED NON-LINEAR CONTROL AND ESTIMATION ALGORITHM FOR ROCKET BASED APPLICATIONS - JAWAHAR A; VISHNU CHAKRAVARTHI CH (Innovare Journal of Engineering and Technology, 2017)
Online Object tracking is an important task in radar and sonar signal processing As it Â is a challenging problem due to the presence of noise, and dynamic changes. a variety of Stochastic algorithms for tracking targets have been proposed and implemented to reach Â these challenges. Approaches towardsÂ Â highly nonlinearÂ applicationsÂ is an Â Â advancedÂ Â task . In this paper, we devote the effort to use the Particle Filtering with estimation of various states of a vehicle launched from an idealized spherical, airless, non-rotating earth to improve tracking efficiency. The simulation results show that the PF improved the tracking performance compared to the Kalman based Filters (EKF, UKF) for the rocket launch application.